"The Long Shadow of a Juniper Berry": The Poetics of Land-Based Research - Bartlett, Stephanie (Art/Research International)

(untitled) (University of Alberta, 2023)
The purpose of this article is to focus on one land-based, poetic experience at the Blackfoot cultural site Aisinai’pi, Writing on Stone Provincial Park in Alberta, Canada. The focus is on an experience with two participants in the research, the Elder and the artist, who are both working with the school involved on this journey and me, the researcher. To situate the article as part of a research study, I also share the context of the broader qualitative study that works within an Indigenous paradigm to explore the development of kinship between children, the land, and each other. My question in this article is this: How do the poetics of land open new possibilities of how to cultivate a kinship ecology with children? I engage poetic inquiry and life writing to illuminate how this experience on the land gave meaning to and shaped the rest of the research study as it unfolded with children, teachers, an artist, and the Elder who guides the work.